2021
DOI: 10.1002/ardp.202100085
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine‐derived VEGFR‐2 inhibitors: Rational design, synthesis, anticancer evaluations, in silico ADMET profile, and molecular docking

Abstract: Novel pyridine‐derived compounds (5–19) were designed and synthesized, and their anticancer activities were evaluated against HepG2 and MCF‐7 cells, targeting the VEGFR‐2 enzyme. Compounds 10, 9, 8, and 15 were found to be the most potent derivatives against the two cancer cell lines, HepG2 and MCF‐7, respectively, with IC50 = 4.25 and 6.08 µM, 4.68 and 11.06 µM, 4.34 and 10.29 µM, and 6.37 and 12.83 µM. Compound 10 displayed higher activity against HepG2 cells than sorafenib (IC50 = 9.18 and 5.47 µM, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Anastrozole containing a 1,2, 4-triazole ring is used in the treatment of postmenopausal women with estrogen-responsive breast cancer. [24] On the basis of the earlier findings and in continuation of our previous research in anticancer agents, [25][26][27][28][29][30][31][32][33][34][35] especially DNA intercalators, [36][37][38][39] we reported herein DNA-binding and docking studies of a new series of [1,2,4]triazolo [4,3-c]quinazoline derivatives as anticancer agents.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Anastrozole containing a 1,2, 4-triazole ring is used in the treatment of postmenopausal women with estrogen-responsive breast cancer. [24] On the basis of the earlier findings and in continuation of our previous research in anticancer agents, [25][26][27][28][29][30][31][32][33][34][35] especially DNA intercalators, [36][37][38][39] we reported herein DNA-binding and docking studies of a new series of [1,2,4]triazolo [4,3-c]quinazoline derivatives as anticancer agents.…”
Section: Introductionmentioning
confidence: 85%
“…On the basis of the earlier findings and in continuation of our previous research in anticancer agents, [ 25–35 ] especially DNA intercalators, [ 36–39 ] we reported herein DNA‐binding and docking studies of a new series of [1,2,4]triazolo[4,3‐ c ]quinazoline derivatives as anticancer agents.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, our compounds were assessed for their VEGFR-2 inhibitory effects by applying an anti-phosphotyrosine antibody with the Alpha Screen system (PerkinElmer, Waltham, MA, USA) [67,68]. The results are described as IC 50 (50% inhibition concentration value) in Table 3.…”
Section: In Vitro Assay Of Vegfr-2 Kinasementioning
confidence: 99%
“…Such compounds are of interest as starting materials for the preparation of polyazaheterocycles with a bridging nitrogen atom, namely fused 1,2,4-triazines 5 [7,8], 1,2,4,3-triazaphospholo [1,5-a]pyridines 6 [9], [1,2,4]triazolo [1,5-a]pyridines 7 [10][11][12], pyrido [1,2-b] [1,2,4]triazepines 8 [13][14][15][16], and nicotinonitrile derivatives 9 [3] (Scheme 1). Compounds 4 are also promising lowmolecular-weight ligands with an antitumor effect for binding VEGFR-2 kinase [17], phosphodiesterase PDE4 [18], new antibacterial and fungicidal drugs [19], etc. In addition, 1,6-diaminopyridines 4 are used to obtain materials for nonlinear optics [8], azaheterocycles with anticancer action [11,[20][21][22], as well as PGE 2 inhibitors with anti-inflammatory activity [23].…”
Section: Doi: 101134/s1070363221110025mentioning
confidence: 99%